PEMBERDAYAAN ORGANISASI PKK DI KELURAHAN TUMINTING KOTA MANADO - LARASATI, LUCIA; LENGKONG, FLORENCE; LONDA, VERY (Sam Ratulangi University, 2021)
Empowerment is a process in which individuals or groups are able to increase their capacity and ability tounderstand, interpret the problems they face and then be able to determine their needs and translate theminto action by actively participating in the implementation of activities. The purpose of this study was todetermine the implementation of PKK organizational empowerment in Tuminting Village, Manado City. Thisresearch uses descriptive qualitative research methods. The data collection techniques used wereobservation, interviews and documentation. In this research, the data analysis technique used is the dataanalysis technique according to Miles and Huberman. The results of this study indicate the empowerment ofthe PKK program in Tuminting Village has not been going well, the empowerment of many obstacles andobstacles, lack of attention from the government and PKK of Manado city and inadequate facilities, theexistence of capacity building for the community by conducting handicraft making training. In the presencefactor, PKK members are also less interested in some environments, so that the number of PKK members islimited. So it can be concluded that the empowerment of the PKK organization in Tuminting Urban Village,Manado City has not been going well, it can be seen from the program that has not reached half of the tenprograms that the PKK of Tuminting Village must do.Keywords : Empowerment, Organization, PKK